Effect of aerobic training associated with hypoxic exposition during sleep on antioxidant capacity - Pialoux, V.; Mounier, R.; Gueux, E.; Mazur, A.; Rayssiguier, Y.; Coudert, J.; Fellmann, N. (3rd FEPS Meeting, Nice, 28 June - 2 July 2003, 2003)
The aim was to determine, on high-level nordic skiers, the impact of physical training associated with hypoxia during sleep on the antioxidant capacity evaluated by two direct methods and on the production of a lipoperoxidation (malondialdehyde, MDA) marker following an in vitro oxidation. Eleven subjects were divided in 2 groups. The first group (H) (n=6) trained at low altitude (1,100m) and slept in normobaric hypoxic room during 3 weeks: simulating 2,500 m during the first week, 3,000 m the second week and 3,500 m the third week, and the second group (N) (n=5) were submitted to the same training but slept at 1,100 m of altitude. Venous blood samples were collected in pre-training state (I), immediately at the end of training session (II) and 2 weeks after (III). Plasma Trolox equivalent antioxidant capacity (TEAC), ferric reactive antioxidant potential (FRAP) were analysed in I, II and III periods. The difference between MDA induced in vitro (MDA-i) and non-induced (MDAni), considered as an indirect evaluation of plasma antioxidant capacity, was measured in I and III. TEAC and FRAP were decreased by training (I vs II) in both groups (H=-21%, p=0.03, N=-13%, p=0.04 for TEAC and H=-20%, p=0.01, N=-17%, p=0.03 for FRAP). Only TEAC returned to its basal value in III whereas FRAP values remained significantly lower than in I. For each periods, the FRAP and TEAC values were highly correlated (r=0.85, r=0.63 and r = 0.80 for I, II and III respectively). The difference between MDA-i and MDA-ni were higher in III than in I (H=+70%, p=0.04 and N=+59%, p=0.006). No significant differences were found between H and N for each methods. Regardless the methods used, an intense aerobic training was responsible for an antioxidant capacity decrease, which persisted after 2 weeks of recovery and the associated hypoxia did not worsen the deficiency.